Formation of nascent soot and other condensed-phase materials in flames - Wang, Hai (Proceedings of the Combustion Institute, 2011)
Over the last two decades, our understanding of soot formation has evolved from an empirical, phenomenological description to an age of quantitative modeling for at least small fuel compounds. In this paper, we review the current state of knowledge of the fundamental sooting processes, including the chemistry of soot precursors, particle nucleation and mass/size growth. The discussion shows that though much progress has been made, critical gaps remain in many areas of our knowledge. We propose the roles of certain aromatic radicals resulting from localized π electron structures in particle nucleation and subsequent mass growth. The existence of these free radicals provides a rational explanation for the strong binding forces needed for forming initial clusters of polycyclic aromatic hydrocarbons. They may also explain a range of currently unexplained sooting phenomena, including the large amount of aliphatics observed in nascent soot formed in laminar premixed flames and the mass growth of soot in the absence of gas-phase H atoms. While the above suggestions are inspired, to an extent, by recent theoretical findings from the materials research community, this paper also demonstrates that the knowledge garnered through our longstanding interest in soot formation may well be carried over to flame synthesis of functional nanomaterials for clean and renewable energy applications. In particular, work on flame-synthesized thin films of nanocrystalline titania illustrates how our combustion knowledge might be useful for developing advanced yet inexpensive thin-film solar cells and chemical sensors for detecting gaseous air pollutants.